2014
DOI: 10.1021/ja508222m
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Fine Structures of the Electric Double Layer of Electrochemical Interfaces in Ionic Liquids with an AFM Tip Modification Strategy

Abstract: We report enhanced force detection selectivity based on Coulombic interactions through AFM tip modification for probing fine structures of the electric double layer (EDL) in ionic liquids. When AFM tips anchored with alkylthiol molecular layers having end groups with different charge states (e.g., -CH3, -COO(-), and -NH3(+)) are employed, Coulombic interactions between the tip and a specified layering structure are intensified or diminished depending on the polarities of the tip and the layering species. Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 37 publications
3
60
0
1
Order By: Relevance
“…[94][95][96] On the other hand, another set of experiments based on sum frequency generation (SFG) spectroscopy suggested that a Helmholtz-like inner layer largely dominates the EDL structure. For example, Baldelli suggested an interpretation of the SFG spectroscopy of EDL structure 97, 98 that is consistent with the formation of a single strongly adsorbed (Helmholtz-like) layer and not with a multilayer structure.…”
Section: The Electric Double Layer (Edl) Structurementioning
confidence: 99%
“…[94][95][96] On the other hand, another set of experiments based on sum frequency generation (SFG) spectroscopy suggested that a Helmholtz-like inner layer largely dominates the EDL structure. For example, Baldelli suggested an interpretation of the SFG spectroscopy of EDL structure 97, 98 that is consistent with the formation of a single strongly adsorbed (Helmholtz-like) layer and not with a multilayer structure.…”
Section: The Electric Double Layer (Edl) Structurementioning
confidence: 99%
“…Introduction of overscreening into the theory [8] leads to a complicated set of equations, but its effect on capacitance is tricky: although it broadens somewhat the capacitance curve, alone, without the introduction of the compact layer, it does not substantially reduce the 1 Their existence has also been detected directly by X-ray [6,[45][46][47][48][49] and indirectly by scanning nano-probe techniques [50][51][52][53][54][55][56]. Generally, oscillating profiles and overscreening in dense ionic solutions have a long history.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of Refs. 72-74 studied the effects of short-range correla-2 Experimental verifications of oscillating structures in the double layer of ionic liquids [6,[45][46][47][48][49][50][51][52][53][54][55][56] have all been detected near ideally atomically flat surfaces, and we are not aware of any systematic investigations of how they may be perturbed or eliminated by the atomic roughness of the surface [56]. However, computer simulations have specially studied step-edge defects in carbon electrodes [65,66] and surface roughness on a similar scale to molecular dimensions [5,67], which have demonstrated that the resonance effect could be damped.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years numerous efforts have gone toward understanding the complex structure of ILs at the solid-liquid interface using both theoretical approaches6789101112 and experimental methods such as scattering techniques131415, sum-frequency generation161718, surface-force apparatus19202122232425, and scanning probe techniques. For the latter, scanning tunneling microscopy (STM)2627282930313233343536 and dynamic3738394041 and static42434445464748495051 atomic force microscopy (AFM) approaches have made large progress towards imaging the ion layers in two and three dimensions at neutral and charged surfaces such as mica, silica, gold, and highly-oriented pyrolytic graphite (HOPG). Scanning probe microscopy based techniques offer the advantage of high spatial resolution in three dimensions compared to other techniques, allowing for the ion structure to be visualized in a 3D manner, as opposed scattering techniques and SFA where the response is averaged over large areas.…”
mentioning
confidence: 99%